So You Want to Set Up Your Scholarly Communications and Research Division - K. A. McCormick (20584421) (2025)
Lessons learned from two librarians who started a new unit within their academic library to meet the university's scholarly communications needs. This presentation was delivered at the Third Annual Forum for Open Research in MENA in October 2024 hosted at Qatar National Library. Other Information Conference information: The Third Annual Forum for Open Research in MENA License: https://creativecommons.org/licenses/by/4.0/ See conference program: 2024 Annual Forum - Forum for Open Research in MENA